Ddx3xa mutations drive cardiac defects in a zebrafish model via dysregulation of wnt/β-catenin signaling - Chen, Yu; Lin, Mei; Zhu, Ping; Wang, Haochen; Jiao, Zhongbei; Yi, Kexing; Yang, Xueting; Zhang, Yingshuo; Cai, Xiaoyan; Yuan, Wuzhou; Li, Yongqing; Jiang, Zhigang; et al. (Frontiers in Molecular Biosciences, 2025)
IntroductionMutations in the DDX3X gene are the primary cause of DDX3X syndrome, with over 800 diagnosed families worldwide. DDX3X is also recognized as a single-gene driver for rare syndromes associated with epilepsy, autism, and developmental disorders. Clinical studies suggest potential links between DDX3X mutations and various cardiac comorbidities. However, there is no report on whether Ddx3xa knockout leads to cardiac phenotypes or whether a zebrafish ddx3xa gene knockout model has been used for such research. This study is based on the high genomic conservation between zebrafish and humans, utilizing a zebrafish model to investigate the potential links between DDX3X mutations and various cardiac comorbidities, as well as the underlying mechanisms.MethodsA ddx3xa knockout model was constructed using CRISPR/Cas9 technology. To elucidate the molecular mechanisms, we performed transcriptome-wide profiling via RNA-Seq to identify differentially expressed genes and dysregulated signaling pathways. The spatiotemporal expression patterns of key genes were assessed using whole-mount in situ hybridization (WISH). Additionally, the critical role of Wnt/β-catenin signaling in the mutant phenotype was further validated using the Wnt inhibitor IWR-1.ResultsHomozygous knockout (ddx3xa−/−) embryos exhibited developmental delay, trunk malformations, and severe cardiac abnormalities, including pericardial edema, defective cardiac looping, and cardiac contractile dysfunction. Ribonucleic Acid Sequencing (RNA-seq) analysis of ddx3xa−/− zebrafish at 72 h post-fertilization (hpf) revealed significant enrichment in pathways related to actin cytoskeleton organization, calcium signaling, cardiac and vascular smooth muscle contraction, and Wnt signaling. Quantitative Real-Time Reverse Transcription Polymerase Chain Reaction (QRT-PCR) and in situ hybridization confirmed dysregulated expression of key cardiac development genes (bmp4, actn2b, tbx5, nppb) and significantly impaired cardiac function. Given the role of Wnt signaling in cardiogenesis, we further analyzed this pathway and found that ddx3xa knockout upregulated the key Wnt/β-catenin transcription factor Tcf/Lef1 (T Cell Factor/Lymphoid Enhancer Factor 1) and disrupted its target genes (bmp4, tbx5) expression. Crucially, treatment of 72 hpf mutant embryos with the Wnt inhibitor IWR-1 partially rescued both the cardiac malformations and the aberrant expression of its target genes.DiscussionThis study provides the first evidence that ddx3xa regulates cardiac morphogenesis by modulating the Wnt/β-catenin signaling pathway, offering direct experimental insight into the mechanisms underlying cardiac comorbidities in DDX3X syndrome. It also highlights the unique value of the zebrafish model for dissecting conserved pathogenic pathways and exploring targeted therapeutic strategies.